VD_FINDINFO Jug / 2016 / 25 vom 14. August 1996 - VD Tribunal cantonal (1996)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, PRESCRIPTION, INTERRUPTION DU DÉLAI | 130 al. 1 CO, 321e CO, 60 CO, 97 CO, 16 al. 3 LPers-VD, 2 al. 1 LPers-VD, 9 LRECA